PERGANTIAN CHIEF EXECUTIVE OFFICER (CEO) DAN KINERJA AKUNTANSI (Studi Empiris pada Perusahaan Non-Keuangan yang Listing di BEI Tahun 2001-2012) - Putri Meelyana Novitasari; Sri Suranta; Doddy Setiawan (Jurnal Akuntansi, 2015)
The purpose of this research is intended to provide evidence that there is a change in the performance of accounting and corporate restructuring after Chief Executive Officer (CEO) turnover. Accounting performance used earnings (ROA and ROE) and leverage. Restructure used the employees and total assets. The sample is a non-financial companies listed in BEI in 2001-2012. The study is also divided by origin CEO’s been inside and outside, as well as compare with industry trends. The sample used purposive sampling methode, and for testing used the T-test. Of all non - financial companies listed in BEI the period 2001-2012, there were 299 companies that did the CEO turnover. The samples can be used as much as 126 companies are divided into 77 companies turns inside and 49 outside the company turnover. The results of the research indicated that overall there is a changes in the accounting performance and corporate restructuring after CEO turnover. When viewed from the origin of the CEO, outside is better than inside. Keyword: CEO turnover, accounting performance, restructuring, inside and outside CEO.